Genetic structure analysis and core germplasm construction of Robinia pseudoacacia and its closely related species based on SNP - Haoran Wang; Yan Ma; Ruixue Wang; Dekui Zang; Xiaoyan Yu; Jingtao Li; Qichao Wu; Fengqi Zang (BMC Plant Biology)
Abstract Robinia pseudoacacia is a forest biomass energy tree species with substantial potential for development and utilization. However, the lack of research on its genetic structure and the unclear genetic background of its germplasm resources impede the conservation and improvement of R. pseudoacacia. In this study, Hyper-seq was used to identify the SNP of Robinia spp. (R. pseudoacacia and its closely related species). The genetic diversity and population structure of 105 Robinia spp. germplasm were analyzed, and a core germplasm bank was constructed. A total of 1,298,097 SNPs and 306,188 InDel polymorphic loci were obtained via mapping with the reference genome. Most of the mutations were detected in the intergenic region. For the 101 R. pseudoacacia samples, the polymorphism information content (PIC) was 0.100 and the nucleotide diversity (Pi) was 0.178, indicating a relatively low level of genetic diversity. Population genetics analysis was conducted based on the 1,312 filtered SNP loci. Phylogenetic relationships divided the entire population into three groups. Genetic structure and cross-validation error indicate low genetic divergence among the sampled individuals. Finally, 21 samples were selected as the core germplasms, accounting for 20% of the total samples. This study provided the basis for genetic research, germplasm protection and breeding of Robinia spp.